A retrospective study on transabdominal ultrasound measurements of the rumen wall thickness to evaluate chronic rumen acidosis in beef cattle - Enrico Fiore; Vanessa Faillace; Massimo Morgante; Leonardo Armato; Matteo Gianesella (BMC Veterinary Research, 2020)
Abstract Background Chronic and subacute rumen acidosis are economically important in the beef industry. The aim of this study was to evaluate the potential suitability of the transabdominal ultrasonographic examination of the ruminal wall to diagnose chronic rumen acidosis in beef cattle compared to direct measurement of ruminal pH, as a fast non-invasive tool to be used in field condition. Ultrasonographic examination of the rumen was conducted in 478 beef cattle before rumenocentesis (chronic rumen acidosis group = pH ≤ 5.8; healthy group = pH ≥ 5.9). Rumen wall ultrasound measurements included rumen wall thickness (RWT) and rumen mucosa and submucosa thickness (RMST). Results The Analysis of Variance showed the high significant effect of the pH class for RWT and RMST (P < 0.001). Spearman RANK correlation analysis showed interaction between rumen pH and RWT (− 0.71; P < 0.0001) and RMST (− 0.75; P < 0.0001). A significant Spearman’s correlations were found between volatile fatty acids (VFA) and RWT and RMST. The differentiation efficiency of RWT between healthy and chronic rumen acidosis groups, as a result of the receiver operator curve (ROC) analysis, was quite good with an area under the receiver operator curve (AUROC) of 0.88: P < 0.0001; 95% CI: 0.83–0.98. Using a cut-off value of > 8.2 mm. The differentiation efficiency of RMST between healthy and chronic rumen acidosis groups, as a result of ROC curve analysis, was good with an AUROC of 0.90: p < 0.0001; 95% CI: 0.85–0.94. Using a cut-off value of > 5.3 mm. Conclusions In this study, the thickening of RWT and RMST is correlated with the changes of ruminal pH. Transabdominal rumen ultrasound has the potential to become a powerful diagnostic tool useful to identify fattening bulls affected by chronic rumen acidosis.